Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4825054
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of Cr-diluted CoFeB

Abstract: Abstract:The crystallization process and the magnetization of Cr diluted CoFeB was investigated in both ribbon samples and thin film samples with Cr content up to 30 at. %. A primary crystallization of bcc phase from an amorphous precursor in ribbon samples was observed when the annealing temperature rose to between 421 ˚C and 456 ˚C, followed by boron segregation at temperatures between 518 ˚C and 573 ˚C. The two onset crystallization temperatures showed strong dependences on both Cr and B concentrations. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Further, we assumed the damping constants are same as those used in Section V. One possibility of reducing the saturation magnetization of CoFeB (which is the most common material used for the MTJs) is to dilute CoFeB by adding Cr to it. It has been shown that CoFeCrB can have saturation magnetization anywhere between 1000 emu/cc to 100 emu/cc based on the percentage of Cr in the sample [44]. One should, however, be careful while dealing with materials having low saturation magnetization.…”
Section: A Predictive Scaling Trends For I-mtjsmentioning
confidence: 99%
“…Further, we assumed the damping constants are same as those used in Section V. One possibility of reducing the saturation magnetization of CoFeB (which is the most common material used for the MTJs) is to dilute CoFeB by adding Cr to it. It has been shown that CoFeCrB can have saturation magnetization anywhere between 1000 emu/cc to 100 emu/cc based on the percentage of Cr in the sample [44]. One should, however, be careful while dealing with materials having low saturation magnetization.…”
Section: A Predictive Scaling Trends For I-mtjsmentioning
confidence: 99%
“…In the last years, several reports on doped CoFeB alloys have proven the potential of this approach. The introduction of Cr results in a strong reduction of M S [8][9][10], however, it is sometimes also causing an increase of the damping parameter [8]. The reduction of M S by doping CoFeB with Ni is smaller compared to a doping with Cr but it additionally leads to a reduction of α [8].…”
mentioning
confidence: 99%